THE IMPROVING OF PEER FEEDBACK TECHNIQUE ON STUDENTS’ WRITING ABILITY AT THE SEVENTH GRADE STUDENTS OF SMP TAMAN ASUHAN PEMATANGSIANTAR - MARHAENI MATONDANG (LP2MTBM MAKARIOZ, 2019)
The research focused on The Improving of Peer Feedback Technique on Students’ Writing Ability at the seventh grade students of SMP Taman Asuhan Pematangsiantar. The problem of this research is: How is The Improving of Peer Feedback Technique on Students’ Writing Ability at the seventh grade students of SMP Taman Asuhan Pematangsiantar in academic year 2019/2020?Some theories were used to answer the research problem, they were: Suharsimi Arikunto (2002), H.D Brown (2001), L Ferris (1995), Harmer, J (2004), J. Liu. and J. Hansen (2002), T.M Paulus (1999), Artono Wadiman and His friend. (2008). This research design was quantitative method by following pre-experimental and pre-control design of two group pre-test-post-test. The population was 337 students and the sample was taken by control sampling technique and experimental got VII/A and VII/B with 35 students. The instrument was essay test. The data analysis started from scoring composition, calculating the validity and reliability, finding variants and mean difference, calculating standard deviation difference deviation and standard error difference.Based on the data analysis, it was found that the treatment of peer feedback technique, students’ prior knowledge in writing descriptive text was low since the pre-test data was 1744 and the mean was 49,9 and after the treatment, it had been improved since the post-test data was 2677and the mean was 76,48.After analyzing the data, it was concluded that the use of peer feedback technique gives significant contribution in improving students’ competence in writing descriptive text at the seventh grade students of SMP Taman Asuhan Pematangsiantar in academic year 2019/2020. So, every English teacher should use peer feedback technique in teaching writing descriptive text because it had been proved that it gave significant contribution in improving students’ competence in writing descriptive text and each teacher should choose appropriate method firstly before teaching.